The Properties of Historic Mortar and Plaster in the Historic City of Ayutthaya World Heritage Site - วัสสันตชาติ, นวลลักษณ์ (NAJUA: Architecture, Design and Built Environment, 2018)
The Properties of Historic Mortar and Plaster in the Historic City of Ayutthaya World Heritage Site Nuanlak Watsantachad Faculty of Architecture, Silpakorn University This research aims to characterize historic mortar and plaster found on ancient monuments of the Historic City of Ayutthaya World Heritage Site compared with the characteristics of modern materials specified by the Fine Art Dapartment for restoring the momuments sufferring from the 2014 Great Flood and in the past with the assumption that the properties of the studied historic mortar and plaster could lead to a standardization of the properties of modern mortar and plaster appropriate for the restoration of the monuments in this world heritage site. However, the research results show that, except being mainly composed of lime and sand, the other properties of the historic mortar and plaster vary from monument to monument regardless of the periods or styles of art and architecture. Hence, there is no starndard modern mortar and plaster that could be used in every Ayutthaya’s restoration project. Studying the properties of each monument’s materials prior to considering appropriate modern materials to be used for restoring them is therefore mandatory.